2014
DOI: 10.4172/2157-7536.1000146
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Low Frequency Pulsating Magnetic Fields of Different Parameters on the Secretion of FSH, LH, Prolactin, Testosterone and Estradiol in Men

Abstract: The research into the effects of low frequency magnetic fields on living organisms has focused so far on the fields produced by power lines, industry and mobile telecommunication. Although they may influence procreation and teratogenesis, the pulsating magnetic fields that are used in physical therapy have not been sufficiently studied with regard to their impact on the endocrine system Aim: The aim of the study was to test the influence of magnetic fields applied in long-term magnetotherapy and magnetostimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Another study reported that serum progesterone, estrogen, and FSH levels decreased in female rats exposed to a 50-Hz sinusoidal magnetic field for 18 weeks [ 46 47 ]. Similarly, Woldanska-Okonska et al demonstrated a decrease in blood progesterone, prolactin and estrogen levels in men resulting from exposure to 50 Hz EMF [ 48 ]. Another experimental study observed no changes in serum prolactin levels in men following short-term exposure to 900-MHz EMF [ 49 ].…”
Section: Effect Of Emf On Enzymatic Activitymentioning
confidence: 99%
“…Another study reported that serum progesterone, estrogen, and FSH levels decreased in female rats exposed to a 50-Hz sinusoidal magnetic field for 18 weeks [ 46 47 ]. Similarly, Woldanska-Okonska et al demonstrated a decrease in blood progesterone, prolactin and estrogen levels in men resulting from exposure to 50 Hz EMF [ 48 ]. Another experimental study observed no changes in serum prolactin levels in men following short-term exposure to 900-MHz EMF [ 49 ].…”
Section: Effect Of Emf On Enzymatic Activitymentioning
confidence: 99%
“…Numerous investigations, from monitoring changes at molecular levels to the behavioral aspects, have been carried out in vitro and in vivo in order to illustrate different effects of ELF/EMF e.g., its impacts on cells, 1 hormones, [2][3][4][5][6] neurophysiological properties and sleep, 7,8 biochemical factors and metabolism, 9-11 pathology, 12,13 DNA damages and chromosome abnormalities, [14][15][16][17][18][19] reproduction and development, 20 and cancer. [21][22][23] On the other hand, the fact that central nervous system (CNS) as a very complicated electrochemical system may be influenced by electromagnetic fields attracts many researches interests.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that magnetotherapy might distort the electromagnetic field of cells, and thus influence neurohormonal patterns or mechanisms of volumetric extra-synaptic transport should also be considered. There are data indicating that the former effect does not occur (62), whereas there is no information concerning the latter.…”
Section: Electromagnetic Energymentioning
confidence: 90%